Understanding the role of immune-mediated inflammatory disease related cytokines interleukin 17 and 23 in pregnancy: A systematic review - Aniek Plug; Liana Barenbrug; Bart G.J. Moerings; Elke M.G. de Jong; Renate G. van der Molen (Journal of Translational Autoimmunity)
Background: Pregnancy requires a careful immune balance between tolerance for the semi-allogenic fetus and protection against pathogens. Women with immune-mediated inflammatory diseases (IMIDs), where the interleukin (IL)-23/IL-17 axis plays an important role, often experience changes in disease severity during pregnancy. These changes and the association between disease flares and pregnancy complications, suggests a role for IL-17 and IL-23 in pregnancy. Methods: We systemically searched PubMed, EMBASE, and Web of Science (March 2024), to assess the role of IL-17 and IL-23 in pregnancy-related in vitro assays, animal or human studies. Results: Eighty articles (8 in vitro, 11 animal and 61 human studies) were included. Seventy-one studies reported on IL-17 and 16 studies on IL-23. In vitro trophoblast proliferation, migration and invasion was increased in the presence of IL-17, but impaired with IL-23. IL-17 levels were increased in animal models for pregnancy complications. In humans, IL-17 levels seemed to be increased in pregnant women versus non-pregnant women. Additionally, elevated IL-17 levels were associated with pregnancy complications. Although similar trends were found for IL-23, data were limited. Conclusions: We identified a large, but heterogenic, body of evidence for a significant role of IL-17 in all stages of pregnancy: while an excessive increase seemed to be associated with complications. The limited number of studies prevents firm conclusions on the role of IL-23. Future research is needed to find biomarkers for patients with IMIDs to predict the effect of possible disease flares on pregnancy, and the effect of therapeutic inhibition of IL-17 or IL-23.